Komunikasi Internal BUMN dalam Menjembatani Kesenjangan Generasi: (Studi Kasus Mengenai Interaksi Antargenerasi di Lingkungan Kerja PT Taman Wisata Candi Borobudur, Prambanan dan Ratu Boko) - Erni Irdewanti; Yustikasari; Siti Karlinah (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
As Indonesia's workforce is dominated by Generations Y and Z, understanding and managing such generational differences is crucial for organizations today. This study explores intergenerational communication at PT TWC, a state-owned enterprise, and analyzes the company's efforts to bridge the generational gap. Using a qualitative approach, the researchers conducted observations and interviews with teams managing internal communication. The findings show the communication gap is driven by differences in values, mindsets, and technology preferences between Generations X, Y, and Z. To address this, PT TWC developed an internal "Percaya" campaign with seven programs across formal media (intranet portal, internal social media, town hall meeting) and informal media (community activities and internal sharing sessions). The campaign is led by a task force team from the "cusper" generation, seen as competent to implement programs bridging the intergenerational divide.